Pengaruh Pembelajaran Matematika Menggunakan Model Problem Based Instruction Terhadap Hasil Belajar Segitiga (JURNAL PENELITIAN PENDIDIKAN MATEMATIKA, 2023)
The problem in this study is "is there an effect of learning mathematics through the Problem-Based Instruction (PBI) model on triangle material on the learning outcomes of VII grade students of MTs Negeri 1 Palembang?". The purpose of this research is to find out: (1) the effect of the problem-based instruction learning model and the conventional model in terms of learning outcomes of seventh-grade students in MTs Negeri 1 Palembang; (2) whether there is a difference in the effect between learning model with problem-based instruction and conventional teaching model in terms of learning outcomes of seventh-grade students in MTs Negeri 1 Palembang. This research is a type of experimental research with a population of all seventh-grade students of MTs Negeri 1 Palembang. The sample consisted of two classes taken by random sampling technique. The triangle learning outcomes data obtained were analyzed using a one-sample t-test and an independent sample t-test. The results showed: (1) problem-based instruction and conventional learning models each have an effect seen from the learning outcomes of triangles of students in class VII MTs Negeri 1 Palembang. Based on statistical analysis, it was found that "learning mathematics through learning the Problem-based instructional model on the learning outcomes of triangles in class VII MTs Negeri 1 Palembang" was accepted.